A Transformer using two RDL metal layers based on Fan-Out Panel Level Package Technology. Issue 1 (July 2021) - Wang, Zixu; Niu, Xulei; Lin, Shaopan; Lin, Tingyu; Huang, Guochi
Abstract: Under the background that electronic products have been developing in the direction of being smaller, lighter and cheaper, the packaging of chip components has also been continuously improved. Fan-out panel-level package (FOPLP) is one of the latest development trends in microelectronics package, which can achieve higher productivity and lower costs. A planar toroidal spiral transformer is designed based on Fan-Out Panel Level Package technology. The transformer is constructed by two RDL layers provided by the packaging process. The size of the proposed transformer is 434um×434um. The simulated primary and secondary inductance is 2.5nH and 2.5nH respectively. The coupling factor of the transformer is 0.845. The quality factor of the transformer is higher than 800 during the entire working frequency range. The self-resonant frequency of the present transformer is 20 GHz. Compared to the on-chip counterpart, the transformer designed based on Fan-Out Panel Level Package technology can achieve higher coupling factor and quality factor. Therefore, the proposed transformer can save chip size and reduce the cost through avoiding using area hungry passive on chip transformer.